Diversity in the Bioaccessibility of Carotenoid and Chlorophyll Compounds in 69 Spinach Genotypes (P06-007-19). (13th June 2019) - Hayes, Micaela; Pottorff, Marti; Kay, Colin; Deynze, Allen Van; Osorio-Marin, Jualiana; Lila, Mary; Iorrizo, Massimo; Ferruzzi, Mario
Abstract: Objectives: Spinach is one of the most nutrient dense and popular green leafy vegetables. Known as a rich source of pro-vitamin A carotenoids and chlorophylls, the variation in content of these bioactives has been associated with differences in genetics, environment and processing. However, beyond processing, factors affecting their bioavailability remain relatively unknown. Establishing the presence of diversity in bioaccessibility, a phenotypical surrogate for bioavailability, of phytochemicals from public germplasm collections and commercial cultivars would provide critical information to breeders seeking to improve the nutritional value of the material used in their programs. Methods: 69 spinach accessions from both the USDA Germplasm Resource Information Network (GRIN) and the Center for Genetic Resources (CGN), the Netherlands, and selected commercial varieties were greenhouse-grown during the Fall 2018 season at Piedmont Research Station, NC, harvested, washed, blanched (100°C, 2 min) and homogenized (30 sec). Carotenoid and chlorophyll bioaccessibility were determined from spinach homogenates formulated with 5% canola oil using a high-throughput, three-phase in vitro digestion followed by centrifugation and filtration to isolate the micellar fraction. Transfer of lutein (LUT), β-carotene (BC) and pheophytin A (Phe A) and B (Phe B) from spinach to micellar fractions was quantified by LC to determine bioaccessibility. Results: LUT and BC were well recovered through in vitro digestion while chlorophylls were quantitatively converted to corresponding pheophytins. Relative bioaccessibility for all phytochemicals was found to be significantly different across genotypes, as determined by ANOVA analysis. LUT bioaccessibiltiy ranged from 9.4–30.6% (P = 0.01), BC (12.9–42.5%; P < 0.001), PheA (24.5–51%; P = < 0.001), and PheB (19.8–46.9% P = < 0.001). Absolute bioaccessible content ranged from 0.6–8.2 and 0.9–3.7 mg/100 g fw spinach for LUT and BC, respectively. Conclusions: Results suggest that carotenoid and chlorophyll bioaccessibility may vary based on spinach genotype. The relationship of bioaccessibility to quality traits and potential interactions with agronomic (GxE) and processing (GxP) conditions remain to be explored. Funding Sources: Foundation for Food and Agriculture Research.